PEMANFAATAN AIR BERSIH MASYARAKAT PADA PROGRAM PAMSIMAS DI DESA RAGUKLAMPITAN KABUPATEN JEPARA - Mochammad Qomaruddin; Arie Irvanto Adhi Saputra; Tri Hanafiah Munawaroh; Zurfa Isnaini; Silviana Ika Ariyani (Universitas Muhammadiyah Semarang, 2017)
Before the PAMSIMAS program enters Raguklampitan village, people use shallow wells, springs, and some of them utilizeclean water sources from mobile traders. However, in certain seasons such as drought, wells experience drought so thatpeople rely on water sources from a traveling trader in the form of container 20 liters with a price range of 3500 rupiah. This problem faced by villagers Raguklampitan Jepara on the source of clean drinking water for the needs in every day with low cost and easy utilization. The objectives that can be disclosed in this study are to evaluate the progress of utilization in PAMSIMAS program in Raguklampitan village with quantitative descriptive analysis method. The results of the analysis are Increasing community participation in water tower construction in Plosorejo hamlet increased by 1 unit, BPSPAM Mulya Abadi revenue in managing clean water in the community has increased from 2015 until 2017, and the use of clean water has increased with the increase of water pipeline network through Both wells Gondang Manis and Plosorejo village Raguklampitan District Batealit Jepara regency. Community awareness is excellent when the PAMSIMAS program conducts comprehensive and on-going assistance. Community facilitators play an important role in controlling good programs. Keywords:Clean water, Deep well, Pamsimas